2001
DOI: 10.1046/j.1440-1746.2001.02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vascular resistance assessed by transcranial color Doppler ultrasonography in patients with chronic liver diseases

Abstract: Background and Aim: Cerebral hemodynamic derangement is well known in patients with liver cirrhosis. The advent of transcranial Doppler enables a non‐invasive observation of cerebral hemodynamics. To evaluate the clinical usefulness we examined cross‐sectionally and longitudinally cerebral hemodynamic parameters in patients with cirrhosis. Methods: The subjects of the cross‐sectional study were 117 patients with cirrhosis, 15 patients with chronic hepatitis and 25 healthy controls. The longitudinal study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
4
16
0
4
Order By: Relevance
“…Simultaneously, PI and RI paralleled the severity of HE. As PI reflects the compliance and elasticity of the cerebral vasculature and RI reflects diastolic, systolic, and resistant status of the cerebral vasculature this result suggests that systolic and diastolic cerebral autoregulation is impaired, as PI and RI increased in cirrhotic patients with HE and cerebral hemodynamics was related to severity of HE, consistent with results from previous studies [33, 34]. …”
Section: Discussionsupporting
confidence: 90%
“…Simultaneously, PI and RI paralleled the severity of HE. As PI reflects the compliance and elasticity of the cerebral vasculature and RI reflects diastolic, systolic, and resistant status of the cerebral vasculature this result suggests that systolic and diastolic cerebral autoregulation is impaired, as PI and RI increased in cirrhotic patients with HE and cerebral hemodynamics was related to severity of HE, consistent with results from previous studies [33, 34]. …”
Section: Discussionsupporting
confidence: 90%
“…Kawakami et al (17) showed that increased cerebral vascular resistance, which may change with the severity of hepatic encephalopathy, is directly related to hepatic encephalopathy. They compared 27 patients with hepatic encephalopathy to 26 patients without hepatic encephalopathy and found that the PI and RI levels were higher in patients with hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies show that both indexes are related to changes in peripheral vascular resistances [23-25]. Increased PI is associated with angiographically demonstrated diffuse intracranial vessel disease [26], and both RI and PI have been found to be increased in patients who suffer from diabetes with microangiopathy or advanced cirrhosis with encephalopathy [27,28]. The increased values of PI and RI that we observed in septic patients (compared with control critically ill patients) should be interpreted as a manifestation of enhanced vascular resistance in the cerebral circulation during early sepsis.…”
Section: Discussionmentioning
confidence: 99%